The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/15384101.2015.1064205
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-linked kinase regulates senescence in an Rb-dependent manner in cancer cell lines

Abstract: Anti-integrin-linked kinase (ILK) therapies result in aberrant mitosis including altered mitotic spindle organization, centrosome declustering and mitotic arrest. In contrast to cells that expressed the retinoblastoma tumor suppressor protein Rb, we have shown that in retinoblastoma cell lines that do not express Rb, anti-ILK therapies induced aberrant mitosis that led to the accumulation of temporarily viable multinucleated cells. The present work was undertaken to: 1) determine the ultimate fate of cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 40 publications
0
16
0
4
Order By: Relevance
“…Integrins are heterodimeric cell adhesion receptors, which contain two different chains, α and β subunits [ 13 ]. Integrins mediate a wide variety of cell-cell and cell-matrix interactions that lead to cell migration, proliferation, differentiation and survival [ 14 - 16 ], by modulating the cell signaling pathways of transmembrane protein kinases such as Focal Adhesion Kinase (FAK) [ 17 , 18 ]. Integrin/FAK signal pathway participates in the activation of akt and the inhibition of GSK3β, and then promotes tumorigenesis, cell metastasis and chemoresistance [ 19 - 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Integrins are heterodimeric cell adhesion receptors, which contain two different chains, α and β subunits [ 13 ]. Integrins mediate a wide variety of cell-cell and cell-matrix interactions that lead to cell migration, proliferation, differentiation and survival [ 14 - 16 ], by modulating the cell signaling pathways of transmembrane protein kinases such as Focal Adhesion Kinase (FAK) [ 17 , 18 ]. Integrin/FAK signal pathway participates in the activation of akt and the inhibition of GSK3β, and then promotes tumorigenesis, cell metastasis and chemoresistance [ 19 - 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jiao et al stated that in response to tissue injury, cytokines and chemokines are stimulated, which result in the activation of some downstream transcription factors (TFs) including nuclear factor-κB (NF-κB), activator protein 1 (AP-1), signal transducers and transcription activators 3 (STAT3) and CCAAT enhancer-binding protein (C/EBP), and a large number of genes including promitogenic genes and homeostatic response genes [ 21 ]. Previous research asserted that hepatocytes were activated at 2 h of LR after PH, and their transition from G0 phase to cell cycle occurred at 2–6 h [ 43 ] ILK pathway could activate the nuclear translocation of β-catenin and enhanced the transcription of LEF-1 through integrin-linked kinase pathway, and then increase the activity of Ap-1 which could promote cell proliferation [ 44 , 45 ], and the expression of critical cytokine IL-6 [ 46 , 47 ] which could affect cell proliferation via Stat3 signal pathway. It has demonstrated that transforming growth factor-β (TGF-β) signaling plays a key role in progression and metastasis of HCC [ 48 , 49 ], and it influences the expression of smad4, smad2/3, and β-catenin proteins and regulates cell activities [ 49 ], which indicates that it is important in liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…Human retinoblastoma cell lines (Y79 and Weri-Rb27) and R28 cells were cultured using DMEM+Glutamax (GIBCO), with 10% fetal bovine serum and gentamicin (50 μg/ml) as described. [48, 49] R28 cells were passaged onto poly-D-lysine coated coverslips in 6-well plates prior to ribavirin exposure at a density of 6.0×10 5 cells per well. Cells were incubated at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%